Numerical investigation of CO2 and NOx emission in a CFB combustor with flue gas recycle and oxy-fuel combustion redesign. (19th October 2021) - Li, Zhenxing; Gao, Yangyan; Wu, Shaohua; Hao, Yanhong
Flue gas recirculation (FGR) technology and oxy-fuel combustion strategy are combined to recycle CO2 in a CFB combustor and to limit the emission of NOx and CO2 . The combustion process in O2 /N2 and O2 /CO2 atmospheres is numerically investigated in the CFB combustor. The NOx emission can be effectively reduced using FGR technology both in O2 /N2 atmosphere or O2 /CO2 atmosphere, which is inversely proportional to the FGR ratio. With O2 /CO2 mixtures as the oxidant, the average combustion temperature is lower than that with O2 /N2 mixtures when the mole fraction of O2 is 21%. However, increasing FGR ratio has little effect on NOx emission and CO2 enrichment, even if CO2 gas is enriched in the flue gas. While using O2 /CO2 mixtures as the oxidant, CO2 could account for more than 90 vol.% in the dried flue gas, thus the CO2 can be easily captured from the flue gas.